2018
DOI: 10.1021/acs.est.7b05619
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Biodegradation of the Previously Persistent Artificial Sweetener Acesulfame in Biological Wastewater Treatment

Abstract: The persistence of acesulfame (ACE) in wastewater treatment (and subsequently the aquatic environment) has led to its use as a marker substance for wastewater input into surface water and groundwater. However, ACE degradation of >85% during summer and autumn was observed in nine German wastewater treatment plants (WWTPs). Annual removal performance was more stable in larger plants, enhanced by low biological oxygen demand and impeded by water temperatures below 10 °C. Literature data suggest that the potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
99
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 111 publications
(110 citation statements)
references
References 48 publications
11
99
0
Order By: Relevance
“…Although ACE‐K usage is expected to remain the same and perhaps even increase in certain regions (i.e., China), the emerging profile of its biodegradation and efficient elimination from WWTPs (especially during warm months) suggests that we might even anticipate measurable decreases in the concentration of ACE‐K in surface waters. Indeed, this is the case in some German rivers where reductions of ACE‐K concentrations of between 70% and 80% have been observed for the period of 2011 to 2016 (Kahl et al 2018).…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Although ACE‐K usage is expected to remain the same and perhaps even increase in certain regions (i.e., China), the emerging profile of its biodegradation and efficient elimination from WWTPs (especially during warm months) suggests that we might even anticipate measurable decreases in the concentration of ACE‐K in surface waters. Indeed, this is the case in some German rivers where reductions of ACE‐K concentrations of between 70% and 80% have been observed for the period of 2011 to 2016 (Kahl et al 2018).…”
Section: Discussionmentioning
confidence: 94%
“…A subsample of 3 WWTPs revealed that concentrations of sulfamic acid in the influent and effluent were similar and therefore the degradation of ACE‐K added insignificantly to the normal loading of sulfamic acid discharged into surface waters (typical for municipal WWTPs receiving high loads of sulfamic acid cleaning products). Kahl et al (2018) confirmed the mineralization of ACE‐K to stoichiometric amounts of sulfamic acid in their study of ACE‐K removal and biodegradation in an aerated horizontal flow treatment wetland and an adjacent municipal WWTP using activated sludge. Finally, in follow‐up studies conducted by Kleinsteuber et al (2019), ACE‐K has been shown to be mineralized in a catabolic process and used as the sole C source by bacterial pure strains isolated from WWTP activated sludge identified as Bosea sp.…”
Section: Effects Assessmentmentioning
confidence: 90%
See 2 more Smart Citations
“…Evolutionary novelty can also emerge in populations exposed to synthetic environments created by humans, and, in doing so, perform essential evosystem services (Rudman et al, 2017). For example, the artificial sweetener acesulfame (ACE) is a persistent compound in aquatic environments because it is resistant to microbial-mediated biodegradation both in natural and wastewater treatment environments (Kahl et al, 2018). Recent work suggests that the catabolism of this compound has evolved repeatedly in multiple wastewater treatment plants in Germany (Kahl et al, 2018), possibly associated with a microbial consortium of proteobacterial species (Fig.…”
Section: The Structure Of Evolutionary Processesmentioning
confidence: 99%